Pelayanan Publik Perizinan Online di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Pekalongan - Nur Akhfir Fadhlika; Trianah Sofiani (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Pekalongan City Investment and One Stop Integrated Service (DPMPTSP) Office launched an online-based licensing system called Sistem Perizinan Online, Ringkas, dan Ekonomis (SAKPORE) so that the people of Pekalongan City can take care of their business licensing online. Previously, licensing services still used a manual system which was feared to create increasing risk on data storage, such as corrupted data. The public also required to come to the office to obtain information about what requirements needed when submitting an application, which costs a lot of money, and to make it worse, lack of information about the processing timeframe are still persist in the whole process. Therefore, this study aims to determine the licensing services using the SAKPORE system. The type of research is empirical juridical with a qualitative approach. The data analysis method that being used is data reduction, data presentation, and drawing conclusions. The results conclude that the ease of applying for online licensing using the SAKPORE system at the Pekalongan City Investment and One Stop Integrated Service (DPMPTSP) can shorten service procedures, service completion time frame, and service completion costs.